From silos to scaffolding: engaging and effective social work practice - Keenan, Elizabeth King; Grady, Melissa D. (Clinical Social Work Journal, 2014)
In this final article of the special issue Beyond the Manual: Using Data and Judgment in Clinical Social Work Practice, we extend the discussion regarding the use of data and judgment. We discuss the multiple sources of data used in practice, including research evidence, client perspectives and experience, moment-by-moment process observation, and client feedback regarding progress towards specific, desired outcomes. We move beyond current debates purporting one framework over another to propose a synthesizing framework that situates evidence-based practice, empirically supported interventions and common elements/mapping and adapting practice within a common factors scaffolding framework. This framework provides a way for social workers to effectively make sound judgments using research and client data within the demands of contemporary practice. The article provides a brief overview of the four practice approaches followed by the proposed scaffolding framework and rationale, and concludes with implications for practice, professional education, and research.
6 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/008-863-792-919-992 tex.eissn: [object Object] tex.unique-id: [object Object]
Keywords: Common elements; Common factors; Empirically supported interventions; Empirically supported treatments; Evidence-based practice; Research evidence; dept.swk

Beyond the manual: using research and evidence in social work practice - Grady, Melissa D.; Keenan, Elizabeth King (Clinical Social Work Journal, 2014)
There is a growing divide in social work between those that believe social work interventions should be based on either art or science. We argue that these positions create a false dichotomy within the profession, possibly due to the language associated with clinical work and research. In this introduction article of the Special Issue: Beyond the Manual, we outline the debate within social work around the art and science split and then offer a new approach to framing the issue. We argue that social workers are regularly approaching their work with clients using art and science simultaneously and describe a new frame for the profession. In an effort to articulate and promote this new frame, this special issue was born. This introductory article concludes with a brief description of the topics and articles included in the issue to orient the reader to the content included within it.
11 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/115-623-556-720-515 tex.eissn: [object Object] tex.unique-id: [object Object]
Keywords: Clinical judgment; Common elements; Common factors; Evidence-based practice; empirically-supported interventions; Research; dept.swk

Seeing Through the Eyes of the Other Using Process Recordings - Schneider, Dana A.; Rodriguez-Keyes, Elizabeth; Keenan, Elizabeth King (Clinical Supervision Activities for Increasing Competence and Self-Awareness, 2014)
This chapter describes a two-step process including videotaping and process-recording activities to facilitate self-awareness and the expression of empathy and acceptance toward other points of view. These activities are designed for beginning student clinicians who are currently completing their coursework and their first clinical internship. The first step of videotaping helps clinicians become more aware of their inner thoughts, feelings, beliefs, and personal values. This first step also helps participating clinicians become more aware of their nonverbal communication with clients, helping them assess how their internal experiences of empathy and acceptance match what is being conveyed nonverbally to their clients. The second step of the activity, process recording, helps clinicians reflect on their ability to use self-awareness to analyze their inner experiences and their outer expressions of empathy and acceptance (both verbal and nonverbal) while still being attuned to their clients' communication.
Section: 4 _eprint: https://onlinelibrary.wiley.com/doi/pdf/10.1002/9781394259335.ch4
Keywords: dept.swk; nonverbal communication; process-recording activities; self-awareness; videotaping